2013
DOI: 10.1016/j.celrep.2013.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cell-Derived Neural Cells Survive and Mature in the Nonhuman Primate Brain

Abstract: SUMMARY The generation of induced pluripotent stem cells (iPSCs) opens up the possibility for personalized cell therapy. Here, we show that transplanted autologous rhesus monkey iPSC-derived neural progenitors survive for up to 6 months and differentiate into neurons, astrocytes, and myelinating oligodendrocytes in the brains of MPTP-induced hemiparkinsonian rhesus monkeys with a minimal presence of inflammatory cells and reactive glia. This finding represents a significant step toward personalized regenerativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 29 publications
5
120
1
Order By: Relevance
“…For example, VM tissue isolated from early stage fetuses showed a higher survival rate than that of older stage fetuses (Sladek Jr. et al, 1993b;Collier et al, 2002), as was previously shown in rodents (Fricker et al, 1997;Torres et al, 2007;Torres et al, 2008). Similarly, early DA progenitors derived from primate PSCs (D21-D28 neurospheres) produced larger grafts (Kikuchi et al, 2011) and showed a higher survival rate (Takagi et al, 2005;Wang et al, 2015) than did late DA neurons (D42 neurospheres; Sanchez-Pernaute et al, 2005;Takagi et al, 2005;Kikuchi et al, 2011;Doi et al, 2012;Emborg et al, 2013a). Nevertheless, the survival rate never exceeded 5 %.…”
Section: Number Of Grafted Cells and Survivalsupporting
confidence: 49%
See 2 more Smart Citations
“…For example, VM tissue isolated from early stage fetuses showed a higher survival rate than that of older stage fetuses (Sladek Jr. et al, 1993b;Collier et al, 2002), as was previously shown in rodents (Fricker et al, 1997;Torres et al, 2007;Torres et al, 2008). Similarly, early DA progenitors derived from primate PSCs (D21-D28 neurospheres) produced larger grafts (Kikuchi et al, 2011) and showed a higher survival rate (Takagi et al, 2005;Wang et al, 2015) than did late DA neurons (D42 neurospheres; Sanchez-Pernaute et al, 2005;Takagi et al, 2005;Kikuchi et al, 2011;Doi et al, 2012;Emborg et al, 2013a). Nevertheless, the survival rate never exceeded 5 %.…”
Section: Number Of Grafted Cells and Survivalsupporting
confidence: 49%
“…Accordingly, the content of the grafts from PSC-derived DA neurons is variable, with a usually high proportion of MAP2+ neurons, from which only a small proportion expresses TH (Takagi et al, 2005;Doi et al, 2012;Emborg et al, 2013a). A9 type DA neurons generally maintained their original A9 characteristics upon grafting (Hayashi et al, 2013;Wang et al, 2015).…”
Section: Progenies Of the Grafted Cells In The Host Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Progenitor cells differentiated into neurons, astrocytes, and oligodendrocytes after transplantation and persisted for at least 6 months. These autologous cells induced a minimal inflammatory response, but no functional improvement was reported due to the small size of the graft (20). Rhee et al (21) reported significant motor improvement using reprogrammed and differentiated human iPSCs delivered to rats with striatal lesions.…”
Section: Testing Ipscs In Animal Disease Modelsmentioning
confidence: 99%
“…Nonhuman primate (NHP) induced pluripotent stem cells (iPSCs) have been valuable resources to model iPSC-based cell therapies in clinically relevant settings. [1][2][3][4] The close phylogenetic relationship of NHPs to humans, as well as their size, longevity, and the well-developed understanding of NHP physiology, makes these models very well suited to preclinical iPSC development. The ability to track derivation of tissues from iPSCs is necessary; thus, engineering NHP iPSCs to strongly and stably express reporter genes is desirable for monitoring of autologous or allogeneic transplanted cells in vivo.…”
Section: Introductionmentioning
confidence: 99%